Two-Electron tin centers formed in chalcogenide glasses as a result of nuclear transformations - Bordovsky, G.A.; Kozhokar, M.Y.; Gladkikh, P.V.; Ali, Hapipah Mohd; Seregin, P.P.; Marchenko, A.V. (2010)
The (119m)Sn impurity atoms formed as a result of the radioactive transformation of the (119mm)Sn parent atoms in the structure of glasses in the As-S and As-Se systems and the As(2)Te(3) glass are involved in the glass composition in the form of Sn(4+) ions. The (119m)Sn impurity atoms formed after the radioactive decay of the (119)Sb atoms in the structure of glasses in the As-S and As-Se systems are located in the arsenic sites and play the role of two-electron centers with a negative correlation energy. For the As(2)Te(3) glass, the (119m)Sn atoms formed in a similar manner are electrically inactive. The larger part of the (119m)Sn daughter atoms, which are formed after the radioactive decay of the (119m)Te parent atoms in glasses of the As-S and As-Se systems and in the As(2)Te(3) glass, are located in the chalcogen sites and are electrically inactive. The significant recoil energy of the daughter atoms in the case of decay of the (119m)Te atoms leads to the appearance of displaced (119m)Sn atoms.